Elementary School Teacher’s Reflection Activities and Feedback in the Context of Lesson Study - Sari, Nurratri Kurnia; Marmoah, Sri; Nurhasanah, Farida; Wicaksana, Muhlis Fajar; Hassaouna, Anissa Taouil (Universitas Sebelas Maret, 2023)
This study aims to explore and analyse reflections in the context of Lesson Study, focusing on teacher teaching practices in primary schools. This research uses a qualitative approach with a case study method. Learning activities are still in the form of an assignment system and are not centered on students. Thus, students have not been able to be active in the learning process. In addition, there are still many students who are not disciplined in doing assignments. This study aims to provide insight into effective and efficient reflection and feedback activities on good and correct Lesson Study activities. Therefore, this research is important to be carried out because it can improve learning practices by adjusting appropriate learning strategies for learning activities that need to be improved, improving student learning outcomes by developing teaching strategies and adjusting to students, Lesson Study can help improve the quality of learning better, and can increase student participation in learning through more interactive, innovative, and student-centered learning. The team of teachers can find the best solution by drawing on the experiences experienced by fellow teachers. The teacher team analyzed the problems of grade 4 students, to find the right solution for learning. The collaboration of the teacher team in lesson study can observe and analyze each other's teaching practices. This allows them to give each other constructive feedback and suggestions to improve each other's teaching skills. Reflection in lesson study plays an important role in improving teaching practices and student learning achievement. By doing deep reflection, teachers can identify problems, evaluate their practices, and find appropriate solutions. Reflection also involves critical, logical, and analytical thinking to produce structured and weighty thinking